Analisis Keandalan Main Battery Peshawar CRJ-1000 Di Maskapai Garuda Indonesia - Hardiansyah, Haidar; Franciscus, Freddy; Yuniarti , Endah (FTK UNSURYA, 2024)
The main battery on the CRJ-1000 aircraft is an important component in the aircraft's electrical system. The main battery functions as the main source of electric power when the aircraft is turned off or when the aircraft engine is not operating. If there is a failure in the aircraft's battery it can cause disruption to other systems so that the aircraft cannot fly or Aircraft on Ground (AOG). In Garuda Indonesia's CRJ-1000 aircraft battery, there were several findings where the battery failed before reaching the scheduled removal time. This study aims to analyze the reliability of the CRJ-1000 main battery on the Garuda Indonesia airline. The analytical method is carried out by collecting historical data on main battery failures and calculating the Mean Time Between Failure (MTBF) and Availability values for a certain period. In addition, an analysis was also carried out on maintenance procedures and replacement of the main battery carried out by Garuda Indonesia airline technicians. The results of the analysis show that the MTBF of the CRJ-1000 main battery on Garuda Indonesia airlines has a fairly good value, but there is a need for improvement in maintenance procedures and replacement of the main battery to increase availability. The recommendations proposed are evaluating the main battery maintenance and replacement procedures, as well as increasing the availability of main battery spare parts which can speed up repair times in failure situations.